Serum Markers of Inflammation Mediate the Positive Association Between Neuroticism and Depression - Schmidt, Frank M.; Sander, Christian; Minkwitz, Juliane; Mergl, Roland; Dalton, Bethan; Holdt, Lesca M.; Teupser, Daniel; Hegerl, Ulrich; Himmerich, Hubertus (Frontiers in Psychiatry, 2018)
Background: The personality trait neuroticism has been implicated in a poor response to stress, may relate to increased concentrations of cytokines and the development of depression. Inflammatory mechanisms may also be associated with the onset, severity and symptoms of depression. Both are related to poor antidepressant treatment outcome. Therefore, mediators of inflammation may bridge the relationship between neuroticism and depression. Methods: To disentangle these interrelationships, the associations between neuroticism (according to NEO-PIR-N), depressive symptoms (BDI-II scores) and serum levels of hsCRP, TNF-α, IFN-γ, IL-2, IL-4, IL-5, IL-10, IL-12, IL-13, GM-CSF were investigated in 212 depressed (n=37) and non-depressed (n=175) participants. A mediation model was used to investigate whether the impact of neuroticism on depressive symptoms may be mediated by cytokines. Results: Regression analyses revealed that IFN-γ, IL-5, and IL-12-levels, but none of the anti-inflammatory cytokines, were associated with the overall neuroticism score and several of the cytokines were related to the different facets of neuroticism. TNF-α, IFN-γ, IL-5, IL-12, and IL-13 were further related to the severity of depressive symptoms, as well as the somatic-affective and the cognitive dimensions of depression. Pro-inflammatory IFN-γ, IL-5 and IL-12 were identified as mediators of the positive prediction of depression severity by the degree of neuroticism. Conclusions: The current findings demonstrate that conditions related to long-term stress, such as depression and high neuroticism, are related to an up-regulation of inflammatory agents. Neuroticism may increase stress perception and, thus, increase the production of pro-inflammatory messenger molecules which are invloved in the development of depression. This evidence may contribute to future anti-inflammatory interventions, particularly in subjects with high neuroticism who are at risk for developing depression. Furthermore, depressed patients may require early escalations in the intensity of treatment, along with additional therapeutic elements to increase the rate of treatment success.